Cultura digital e educação: o caso de educadoras do campo no Centro Rural de Inclusão Digital (CRID) Santana - Santana, Ana Carmen de Souza (2008)
This study attempts to express the systematization of experience in research developed in the Rural Community Santana with its educators in a project Centros Rurais de Inclusão Digital (CRID). The basic assumption was that these people had a digital culture in construction and that it could deepen this issue from a methodology where the object of study is configured with the experiences, thoughts and perceptions that educators draw from their own realities. For this reason, a general theoretical study has been realized about information society in education and after that depth in data analysis with talk of people. The roadmap has been a qualitative research, with an ethnographic approach that used a daily camp as tool for organizing events would contemplate the digital culture of educators in the rural Community Santana in a presence and virtual enviroment. The categories to be considered in aspects of digital culture of the educators to go toward: building practices contextualized to the reality in which they live; planning for CRID educational use and the need for continuing education, which can be made between the same and counting on management group support of CRID and collective perspective to live the CRID as a pedagogical tool for "beyond good will." The experience of CRID is good and we suggest the creation of new socialization spaces for educational practices in CRID by your educator is to give continuity to studies in this area that relation with digital culture and education. The final considerations point to Santanas’s educators that in CRID have a chance to express their autonomy so desired still at school. Another evident aspect was the community, living in the settlement, very expressive in the "struggle to grow and transform" from the CRID.